LCMV-mediated hepatitis in rhesus macaques: WE but not ARM strain activates hepatocytes and induces liver regeneration (2004)
ABSTRACT: Lymphocytic chorimeningitis virus (LCMV), the prototype arenavirus, and Lassa virus (LASV), causative agent of Lassa hemorrhagic fever (LHF), belong to the Old World group of the Arenaviridae. Both viruses have extensive strain diversity and significant variations in lethality and pathogenicity for man and experimental animals. We have shown that the infection of rhesus macaques with the WE strain of LCMV affects liver functions, induces hepatocyte proliferation, and causes a rise in IL-6 and soluble TNF receptors (sTNFR) concomitant with a rise in viremia. The levels of IL-6 and sTNFR can serve as an additional diagnostic tool for liver involvement in pathogenesis of arenavirus infection. Mucosal inoculation of rhesus macaques with LCMV-WE can result in attenuated infection with a transient viremia and liver enzyme abnormalities. The ARM strain of LCMV shares 88% amino acid homology with WE. In contrast to LCMV-WE, ARM strain does not induce manifested disease in monkeys, does not affect liver functions, and does not induce hepatocyte proliferation. Previously we demonstrated that LCMV-ARM infection protected rhesus macaques challenged with LCMV-WE. Here we have shown that the protected animals have no signs of hepatitis and hepatocyte proliferation.